Animal behaviour and dietary preference of dairy cows grazing binary and diverse pastures under the leaf regrowth stage defoliation criterion - Oliveira BA; López FF; Cranston LM; Poli CHEC; Kemp PD; Donaghy DJ; Draganova I; López-Villalobos N (Elsevier B.V., 2024)
In New Zealand, intensively managed pasture-based dairy systems rely on binary pastures mostly comprised of Lolium perenne L. and Trifolium repens L. More frequent and extreme climatic events have been negatively affecting the persistency and production of these pastures, which now present increased seasonality, with marked peaks and troughs of production throughout the year. Diversification of plant species offers a solution to deal with increased seasonality. However, little is known about animal behaviour and dietary preferences of dairy cows grazing diverse pastures. The present study aimed to assess the grazing preferences of dairy cows when unrestrictedly offered binary (L. perenne and T. repens; Bi) and diverse pastures (L. perenne, Bromus valdivianus Phil., Dactylis glomerata L. and T. repens; Mix) subjected to three different leaf regrowth stage (LS) defoliation criteria. Secondarily, the study aimed to determine the main plant-related drivers for any potential animal preference. The treatments were MixLp (defoliated at L. perenne LS), BiLp (defoliated every time MixLp was defoliated), MixBv (defoliated at B. valdivianus LS) and BiBv (defoliated every time MixBv was defoliated), MixDg (defoliated at D. glomerata LS) and BiDg (defoliated every time MixDg was defoliated). Dairy cattle were evaluated over five agricultural seasons. The response variables were grazing time and location, bite rate, animal behavioural activity, pre-grazing herbage mass, undisturbed sward height, lamina:stem ratio, crude protein, metabolisable energy, organic matter digestibility, non-structural carbohydrates, neutral detergent fibre and lignin. Where significant differences were found, binary pastures presented lower sward height and higher non-structural carbohydrate content in comparison to the diverse pastures under the same LS defoliation criteria. However, no significant differences were found in the percentage of time that cows spent grazing both pastures. Season was the greatest contributor to the proportion variation found in all response variables, with values ranging from 47.55 % up to 88.77 %. In winter and spring, cows modulated their grazing behaviour (proportional time spent grazing, ruminating, or idling), investing more time actively grazing pastures under L. perenne LS interval of defoliation (2.5–3.0 LS), the criterion which resulted in shorter grazing rotations. This study allowed us to understand the suitability of diverse pastures from an animal perspective, and highlighted that independent of the pasture type, the positive productive and nutritional effects of defoliation management based on the LS may also extend themselves to positive outcomes in animal preference, interpreted as the percentage of time dairy cows spend grazing rather than ruminating or idling across and within seasons.
Keywords: Grazing behaviour; Dairy cows; Perennial ryegrass; Pasture brome; Cocksfoot; White clover